Splenectomy Alters Distribution and Turnover but not Numbers or Protective Capacity of de novo Generated Memory CD8 T-Cells - Kim, Marie T.; Harty, John T. (Frontiers in Immunology, 2014)
The spleen is a highly compartmentalized lymphoid organ that allows for efficient antigen presentation and activation of immune responses. Additionally, the spleen itself functions to remove senescent red blood cells, filter bacteria, and sequester platelets. Splenectomy, commonly performed after blunt force trauma or splenomegaly, has been shown to increase risk of certain bacterial and parasitic infections years after removal of the spleen. Although previous studies report defects in memory B cells and IgM titers in splenectomized patients, the effect of splenectomy on CD8 T cell responses and memory CD8 T cell function remains ill defined. Using TCR-transgenic P14 cells, we demonstrate that homeostatic proliferation and representation of pathogen-specific memory CD8 T cells in the blood are enhanced in splenectomized compared to sham surgery mice. Surprisingly, despite the enhanced turnover, splenectomized mice displayed no changes in total memory CD8 T cell numbers nor impaired protection against lethal dose challenge with Listeria monocytogenes. Thus, our data suggest that memory CD8 T cell maintenance and function remain intact in the absence of the spleen.